Optimal timing of policy interventions in troubled banks - Philipp Johann König; Paul Mayer; David Pothier (Deutsche Bundesbank, 2022)
We analyze the problem of a policy authority (PA) that must decide when to resolve a troubled bank whose underlying solvency is uncertain. Delaying resolution increases the chance that information arrives that reveals the bank's true solvency state. However, delaying resolution also gives uninsured creditors the opportunity to withdraw, which raises the cost of bailing out insured depositors. The optimal resolution date trades off these costs with the option value of making a more efficient resolution decision following the arrival of information. Providing the bank with liquidity support buys the PA time to wait for information, but increases the PA's losses if the bank is insolvent. The PA may therefore optimally choose to delay the provision of liquidity support in order to minimize its losses.
Keywords: G01; G21; G28; 330; Bank Resolution; Lender of Last Resort; Banking Crises